Review of methodological considerations and recommendations for mapping remote glaciers from aerial photography surveys in suboptimal conditions - D. Medrzycka; L. Copland; L. Thomson; W. Kochtitzky; B. Smeda (Geoscientific Instrumentation, Methods and Data Systems)
The use of structure-from-motion (SfM) photogrammetry coupled with multiview stereo (MVS) techniques is widespread as a tool for generating topographic data for monitoring change in surface elevation. However, study sites on remote glaciers and ice caps often offer suboptimal conditions, including large survey areas, complex topography, changing weather and light conditions, poor contrast over ice and snow, and reduced satellite positioning performance. Here, we provide a review of methodological considerations for conducting aerial photography surveys under challenging field conditions. We generate topographic reconstructions, outlining the entire workflow, from data acquisition to SfM–MVS processing, using case studies focused around two small glaciers in Arctic Canada. We provide recommendations for the selection of photographic and positioning hardware and guidelines for flexible survey design using direct measurements of camera positions, thereby removing the need for ground control points. The focus is on maximising hardware performance despite inherent limitations, with the aim of optimising the quality and quantity of the source data, including image information and control measurements, despite suboptimal conditions.